Use of eye tracking for assessment of electronic navigation competency in maritime training - Oguz Atik; Omer Arslan (Bern Open Publishing, 2019)
The purpose of this study is to experiment an assessment method using eye tracking technology in simulator based electronic navigation training of ship officers who play a critical role in maritime accidents. The maritime industry focuses on human factor developing and improving regulations, training requirements and technology to prevent marine casualties. The mandatory use of simulations in maritime training as per international regulations includes competency assessment as a vital process. The study involves capturing and analyzing eye movement data from ship officers with sea experience in simulation exercises for assessing competency.  A system including an eye tracking analysis software and eye tracking glasses is used for the study. Inferential and descriptive analysis were both used to validate the results. Significant differences were found between electronic navigation competencies of expert and novice ship officers. The results show that the eye tracking technology is a valuable tool for assessment of electronic navigation competency. Comparing novice and expert ship officers' data proves that eye tracking provides in-depth data which is not obtainable by the available observation methods used in simulation training. The findings show that eye tracking provides the assessor novel data, such as focus of attention, which enables evaluation of the cognitive process and competency. The study, therefore, contributes to maritime education aiming to improve the effectiveness of simulator based maritime training which is vital for maritime safety. It also contributes to scientific research on eye movement in maritime field by proposing the integration of eye tracking in competency assessment in electronic navigation training as a part of simulation based maritime education.